2022
DOI: 10.1155/2022/9339325
|View full text |Cite|
|
Sign up to set email alerts
|

A Clinical Diagnostic Value Analysis of Serum CA125, CA199, and HE4 in Women with Early Ovarian Cancer: Systematic Review and Meta-Analysis

Abstract: Objective. To evaluate the value of combined detection of serum CA125, CA199, and HE4 in the diagnosis of ovarian cancer. Methods. Relevant articles retrieved from PubMed, Elsevier Science, Springer, China National Knowledge Infrastructure (CNKI), Wanfang, and VIP databases were screened strictly according to inclusion and exclusion criteria. Included literature published from January 2005 to December 2021. (2) Serum HE4, CA125, CA199, and their combination for ovarian cancer diagnostic tests were studied, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…This leads to a decrease in the PPV; the results from the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial indicated that the PPV for CA125 alone was only 3.7% [ 21 ]. The performance of CA125 varies in different cancer tissue types, with a poor performance in non-epithelial ovarian cancers, clear cell carcinomas, undifferentiated carcinomas, and mucinous carcinomas [ 22 ]. Many other factors can influence serum CA125 levels, leading to variations in the baseline CA125 levels in different women.…”
Section: Current Biomarkers For Ovarian Cancermentioning
confidence: 99%
“…This leads to a decrease in the PPV; the results from the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial indicated that the PPV for CA125 alone was only 3.7% [ 21 ]. The performance of CA125 varies in different cancer tissue types, with a poor performance in non-epithelial ovarian cancers, clear cell carcinomas, undifferentiated carcinomas, and mucinous carcinomas [ 22 ]. Many other factors can influence serum CA125 levels, leading to variations in the baseline CA125 levels in different women.…”
Section: Current Biomarkers For Ovarian Cancermentioning
confidence: 99%
“…Additional tumor markers like CA199 and CEA may also show elevated levels but lack specificity to OC, often associated with gastrointestinal malignancies. 4 While imaging can be used to detect ovarian masses, it cannot make a definitive diagnosis or differentiate benign from malignant lesions, and the lesion cannot be detected until the size reaches a significant level. 5 There remains a deficiency in specificity concerning tumor marker testing alone, transvaginal ultrasound screening alone, or their combined use, which results in unsatisfactory rates of early detection.…”
Section: Introductionmentioning
confidence: 99%
“…The use of blood biomarkers for monitoring cancer status or recurrence, carcinoembryonic antigen (CEA) ( 10 ), carbohydrate antigen 19-9 ( 11 ), human epididymis secretory protein 4 ( 11 ), apolipoprotein A1 ( 12 ), transthyretin ( 13 ), transferrin ( 14 ) and β2-macroglobulin ( 15 ), is well documented. Although these markers could facilitate earlier detection of recurrence, their utility is limited by inadequate sensitivity or specificity ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%